Composition Table Of Moroccan Culinary Recipes - El Mir Nisrine (EDP Sciences, 2021)
Good nutrition plays an essential role in our health. It decreases the risk of developing certain chronic diseases and thus increases life expectancy. This study is the first of its kind in Morocco, its objective is to determine the nutrient composition of the most consumed Moroccan culinary recipes. Thus, thanks to the calculation of the nutriscore, we can know which culinary recipe is the “healthiest”. Some of the most consumed Moroccan traditional dishes were collected in which carbohydrates, fats, and proteins were analyzed using the procedures of the Association of Official Analytical Chemists, then followed by a calculation of the food exchange lists per serving using the Wheeler method. Variations in macronutrients, micronutrients (minerals and trace elements) and trans-fatty acid content, polyunsaturated and monounsaturated were found among the Moroccan dishes. The highest protein (17.37g/100g) in Chicken, French Fries, and Cumin Tajine while the lowest (0.06g/100g) in Orange and Carrot Salad. The highest carbohydrates (42.68g / 100g) in Tuna Pizza while lowest (2.37g / 100g) in tomato with pepper. And the highest lipids (19.2g/ 100 g) in meat with onion Tajine and the lowest (0.6g/ 100g) in Harira. Meanwhile, the energy ranged between 35.7 and 352.4 Kcal/100 g in the dishes. For each dish and according to the size of each serving, the exchanges of carbohydrates (starch), fats, and proteins (lean meat, medium fat, and high-fat meat) were calculated. This study offers an opportunity - for health professionals, dietitians as well as consumers - to orchestrate with knowledge traditional dishes and ensuring leading dietary and medical nutritional therapy practices and patient self-control.